The contribution of hypothalamic macroglia to the regulation of energy homeostasis - Buckman, Laura B.; Ellacott, Kate L. J. (Frontiers in Systems Neuroscience, 2014)
The hypothalamus is critical for the regulation of energy homeostasis. Genetic and pharmacologic studies have identified a number of key hypothalamic neuronal circuits that integrate signals controlling food intake and energy expenditure. Recently studies have begun to emerge demonstrating a role for non-neuronal cell types in the regulation of energy homeostasis. In particular the potential importance of different glial cell types is increasingly being recognized. A number of studies have described changes in the activity of hypothalamic macroglia (principally astrocytes and tanycytes) in response to states of positive and negative energy balance, such as obesity and fasting. This article will review these studies and discuss how these findings are changing our understanding of the cellular mechanisms by which energy homeostasis is regulated.